2007
DOI: 10.1177/001979390706000204
|View full text |Cite
|
Sign up to set email alerts
|

Families, Human Capital, and Small Business: Evidence from the Characteristics of Business Owners Survey

Abstract: An important finding in the rapidly growing literature on self-employment is that the probability of self-employment is substantially higher among the children of business owners than among the children of non-business owners. Using data from the confidential and restricted-access Characteristics of Business Owners (CBO) Survey, we provide some suggestive evidence on the causes of intergenerational links in business ownership and the related issue of how having a family business background affects small busine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
196
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(214 citation statements)
references
References 32 publications
13
196
0
5
Order By: Relevance
“…Through working in a family business, people can acquire certain business ideas and skills to start their own or continue their families' businesses (Basu & Goswami, 1999). In particular, research specifically related to entrepreneurial behavior has shown that entrepreneurs often have a family history where their mother or father was self-employed (Fairlie& Robb, 2007). Even if, in some cases, many entrepreneurs have indicated that they were often placed in positions of responsibility within their family's business at a very young age (Dyer & Handler, 1994).Entrepreneurial parents tend to use the family business as a mean to teach their children the skills, values, and confidence required to own businesses.…”
Section: Determinants Of Entrepreneurship Intentionmentioning
confidence: 99%
“…Through working in a family business, people can acquire certain business ideas and skills to start their own or continue their families' businesses (Basu & Goswami, 1999). In particular, research specifically related to entrepreneurial behavior has shown that entrepreneurs often have a family history where their mother or father was self-employed (Fairlie& Robb, 2007). Even if, in some cases, many entrepreneurs have indicated that they were often placed in positions of responsibility within their family's business at a very young age (Dyer & Handler, 1994).Entrepreneurial parents tend to use the family business as a mean to teach their children the skills, values, and confidence required to own businesses.…”
Section: Determinants Of Entrepreneurship Intentionmentioning
confidence: 99%
“…To my knowledge, only two studies aim at understanding the impact of familial background on small business outcomes (Lentz andLaband 1990, Fairlie andRobb 2007b). Both relate to the USA.…”
Section: Literature Review and Contextmentioning
confidence: 99%
“…Fairlie and Robb (2007b) introduce it but very indirectly, as a component of the inheritance of a family enterprise. They do not formally test it.…”
Section: Literature Review and Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, there is evidence for the positive influence of parental role models (e.g. Fairlie and Robb, 2007). Networks (e.g., Klyver, et al, 2007) and peer groups (e.g.…”
mentioning
confidence: 99%